Bulldog calf born to Limousin-Peranakan-Ongole crossbred cow after insemination with Simmental bull semen - Yuriati (Ovozoa: Journal of Animal Reproduction, 2022)
This case describes a bulldog calf born to Limousin-Peranakan-Ongole (LimPO) crossbred cow after insemination with frozen-thawed Simmental bull semen. The dam was a four year old LimPO crossbred cow, with a bodyweight of 380 kg; she was 8.5 months pregnant and has never had any reproductive disorders before. Signs of impending calving appeared at 6 am, and the discharge was normal, but until noon the calf had not been born. Body temperature was 38°C, while other vital signs were normal. Vaginal exploration revealed a completely opened cervix, and the calf was alive, in posterior longitudinal presentation with palpable short hindlegs. The calf was delivered per vaginam with traction. The calf was male with a weight of 15 kg, and was alive, but after a few minutes, the calf died. The monstrous calf was found with morphological defects including a smaller compressed body, head resembled those of a bulldog with a short muzzle and an undershot jaw, shortened fore- and hindlegs, and ascites abdomen. The dam was given 70, 000 IU procaine penicillin G and 70 mg dihydrostreptomycin sulphate (Penstrep-400, Interchemie, Holland), 0,3 g diphenhydramine HCl (Vetadryl, Sanbe, Indonesia), 10 mg vitamin B12 (Jectavit B12, Sanbe, Indonesia) by intramuscular injection. The dam looked healthy, and had normal appetite after the delivery assistance.